Daptomycin for the treatment of major gram-positive infections after cardiac surgery. Issue 1 (December 2016) - Kornberger, A.; Luchting, B.; Kur, F.; Weis, M.; Weis, F.; Stock, U.; Beiras-Fernandez, A.
Abstract Background Infection is a main cause of morbidity and mortality after heart surgery, with multi-resistant pathogens increasingly representing a challenge. Daptomycin provides bactericidal activity against gram-positive organisms that are resistant to standard treatment including vancomycin. Methods A cohort of cardiac surgical patients, treated with daptomycin for major infection at two tertiary care centers, were retrospectively studied with a particular focus on the type of infection, causative pathogens and co-infections, daptomycin dosage, adverse events and outcome in order to provide evidence for the efficiency and safety of daptomycin in a distinct high-risk patient population. Results Sixty-five patients (87.7 % males, 60.4 ± 13.5 years) who had undergone aortic surgery (20.0 %), ventricular assist device (VAD) implantation (21.5 %), combined procedures (21.5 %), coronary artery bypass grafting (12.3 %), isolated valve surgery (15.4 %) and heart transplantation (7.7 %) were diagnosed with catheter-related infection (26.1 %), valve endocarditis (18.8 %), sternal wound (13.0 %), VAD-associated (11.6 %), cardiac implantable electrophysiological device (CIED)-associated (4.1 %), respiratory tract (4.3 %), bloodstream (4.3 %) and other infection (4.3 %). In 13.0 %, no focus of infection was identified though symptoms of severe infection were present. The most frequent pathogens wereStaphylococcus epidermidis (30.4 %), Staphylococcus aureus (23.1 %) andEnterococcus species (10.1 %). Daptomycin doses ranging from 3 mg/kg every 48 h to 10 mg/kg every 24 h were administered for 15.4 ± 11.8 days. 87.0 % of the cases were classified as success, 7.2 % as treatment failure and 5.8 as non-evaluable. Adverse events were limited to one case of mild and one case of moderate neutropenia with recovery upon termination of treatment. Conclusion Daptomycin proved safe and effective in major infection in high-risk cardiac surgical patients.